TEACHING LISTENING ABILITY BY USING SOMATIC, AUDITORY, VISUAL, AND INTELECTUAL (SAVI) - yuniarti, fatma (STKIP Muhammadiyah Pringsewu, 2018)
The objective of the research is to find out the Effectiveness of using SAVI (Somatic, Auditory, Visual and Intellectual) Technique to teach Listening Ability. The research was a Case Study method. The data from classroom observation were obtained from video recording, studentâs checklist and lecturerâs field notes. The findings of this study showed the use of SAVI (Somatic, Auditory, Visual and Intellectual) Technique is an effective technique for teaching listening Ability.Â Significantly,Â itÂ canÂ beÂ seenÂ thatÂ theÂ studentsÂ enjoyedÂ theirÂ listening.Â As a result, they responded positively and enthusiastically to lesson, and engaged easily in the whole learning process.Â Â